The Symbolic Power Behind Tradition: The Role of Pambiwara in Preserving Javanese Culture - Adi, Yustia Atsanatrilova (Komunitas: International Journal of Indonesian Society and Culture, 2025)
This study explores the role of pambiwara, traditional masters of ceremony, in preserving Javanese cultural heritage in Surakarta, Indonesia. Using a qualitative approach with purposive sampling, in-depth interviews were conducted with 15 informants, including students, teachers, and members of pambiwara courses from September 2 to 15, 2024. The findings shown that pambiwara hold significant cultural authority, which emphasized by the symbolic power which symbolized by the certificate awarded upon course completion. This credential not only affirms mastery of ceremonial practices but elevates its holder’s status, allowing them to conduct important ceremonies like mitoni and weddings. Furthermore, based on Bourdieu theory of symbolism, the study reveals that the certificate confers legitimacy and social prestige, positioning pambiwara as custodians of Javanese cultural traditions. However, as younger generations show increasing interest, challenges in maintaining this exclusivity emerge, underscoring the need for adaptive training methods and formal recognition to ensure the longevity of this cultural practice.